Jiegeng Decoction Potentiates the Anticancer Efficacy of Paclitaxel in vivo and in vitro - Chen, Haifang; Li, Guofeng; Liu, Ye; Lang, Yifan; Yang, Wuliang; Zhang, Wugang; Liang, Xinli (Frontiers in Pharmacology, 2022)
Paclitaxel (PTX) has been the first-line treatment for lung cancer; however, its clinical use is limited due to multidrug resistance (MDR) and adverse effects. Thus, there is an urgent need to explore agents that can enhance the anticancer efficacy of PTX by reducing drug resistance and adverse reactions. Jiegeng decoction (JG) was used as the meridian guide drug and adjuvant drug in treatment of lung cancer. However, the mechanism of adjuvant effect was unclear. The aim of this study was to determine whether JG could potentiate the anticancer effect of PTX. Tissue distribution of PTX was detected using HPLC-MS/MS. The anti-lung cancer effect of the combination of PTX and JG in Lewis lung cancer C57BL/6 mice was evaluated based on the body weight and tumor-inhibition rate. PTX concentration in tumors was determined using HPLC-MS and in vivo imaging. Biochemical indices were detected using biochemical analyzer and ELISA. The anticancer mechanism of the PTX-JG combination in A549/PTX cells was elucidated based on cell proliferation, annexin V-FITC apoptosis assay, and western blotting. Tissue distribution analysis showed that the distribution of PTX increased in the lungs, liver, and heart upon administering the combination of PTX and JG. JG remarkably enhanced the anticancer effect of PTX by increasing the red blood cell and platelet counts; increasing hemoglobin, interleukin (IL)-2, and tumor necrosis factor-α levels; increasing CD4+T cells and the CD4+/CD8+ ratio; and decreasing IL-10 levels. JG administration led to the increased distribution of PTX at the tumor lesion sites and also potentiated the anticancer effect of PTX by inhibiting tumor cell proliferation and promoting apoptosis. Moreover, JG reversed PTX resistance by inhibiting the expression of lung resistance-related proteins, multiresistance protein 1, P-glycoprotein, and breast cancer-resistant protein. Furthermore, the combination of JG and PTX decreased alanine aminotransferase and aspartate aminotransferase levels and did not affect creatine kinase-MB levels. Therefore, our discovery suggests that JG increased the anticancer effect of PTX by downregulating the MDR-related protein and demonstrated a synergistic enhancement of immunity. Thus, the combination of PTX with JG shows potential in the management of lung cancer owing to its synergistic and detoxifying effects.